Paleontology in ecology and conservation - Louys, Julien (Springer Earth System Sciences, 2012)
The fossil record contains unique long-term insights into how ecosystems form and function which cannot be determined simply by examining modern systems. It also provides a record of endangered species through time, which allow us to make conservation decisions based on thousands to millions of years of information. The aim of this book is to demonstrate how palaeontological data has been or could be incorporated into ecological or conservation scientific studies. This book will be written by palaeontologists for modern ecologists and conservation scientists. Manuscripts will fall into one (or a combination) of four broad categories: case studies, review articles, practical considerations and future directions. This book will serve as both a 'how to guide' and provide the current state of knowledge for this type of research. It will highlight the unique and critical insights that can be gained by the inclusion of palaeontological data into modern ecological or conservation studies.